An exploratory study using mindfulness meditation apps to buffer workplace technostress and information overload. Issue 1 (22nd October 2020) - Houli, Daniel; Radford, Marie
Abstract: Information and Communication Technologies (ICTs) have revolutionized the effectiveness and productivity of business and employees. However, ICTs engender stress, including Technostress and Information Overload (IO), which has negative effects on employees' mental and physical well‐being. Companies increasingly are moving toward further integration of ICTs, expedited greatly by the global effects of the COVID‐19 pandemic. To buffer the effects of workplace stress, the authors propose to investigate how app‐based Mindfulness Meditation (MM) can effectively assist individuals dealing with ICTs' negative effects. A preliminary study, involving one IT employee and the popular app "Calm" was conducted to determine the design of a larger, more robust study.